The Risk of Night Shift Workers to the Glucose Blood Levels, Saliva, and Dental Caries - Roestamadji, Retno Indrawati; Nastiti, Nahdah Izdihar; Surboyo, Meircurius Dwi Condro; Irmawati, Anis (European Journal of Dentistry, 2019)
Objective This study aimed to provide the correlation of circadian rhythms of night shift workers with blood glucose levels, saliva, and dental caries.Materials and Methods This study was conducted on night shift and nonshift workers to measure fasting blood glucose (FBG), 2-hour postprandial blood glucose (2-PP BG), saliva flow rate, pH saliva, and caries with the decay-missing-filled total (DMF-T) index. Data analysis was done using independent t-test and correlation test with Pearson correlation.Results There were significant differences in night shift and nonshift workers in FBG (p = 0.000), 2-PP BG (p = 0.000), flow rate saliva (p = 0.000), and DMF-T index (p = 0.001). Correlation test showed positive correlation between FBG and pH saliva (r = 0.42, p = 0.029) and DMF-T index (r = 0.521, p = 0.005) of night shift workers. The 2-PP BG also showed positive correlation with pH saliva (r = 0.493, p = 0.009) and DMF-T index (r = 0.743, p = 0.000). The DMF-T index showed negative correlation with flow rate saliva (r = –0.398, p = 0.04). In the nonshift workers, correlation test showed a correlation between FBG and DMF-T index (r = 0.384, p = 0.048). The DMF-T index showed correlation with flow rate saliva (r = 0.6, p = 0.001).Conclusion There is a circadian rhythm correlation between night shift workers to blood glucose levels, flow rate saliva, pH saliva, and dental caries.
Keywords: circadian rhythm; blood glucose; dental caries; saliva; night shift worker